2016
DOI: 10.1016/j.jcm.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain Response to Pelvic Tilt Position: An Observational Study of Chiropractic Patients

Abstract: Objective: The aim of this study was to look for differences between patients with an increased pain response as compared with those with a decreased pain response. Methods: Data were collected from consecutive new patients with lumbar or lumbopelvic pain in a chiropractic clinic. A pelvic tilt exercise was included in the initial examination, and pain response was noted. Analysis was made of pain and disability severity, as well as symptom location, chronicity, and other characteristics, before and after a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Pelvic tilt exercises designed in sitting and standing position is a low level intensity exercise done to activate the core muscle (internal oblique, external oblique, transverse abdominis, pelvic floor) that are stretched during pregnancy. This co-activation of core muscles imparts active stiffness through thoracolumbar fascia to the lumbar spine and thereby reducing the exaggerated lumbar lordosis which is considered to be one of the causes for lumbar pain during pregnancy [27,28]. Like any other joints in the human body, range of motion and core activation around pelvic joints need to be maintained as well.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic tilt exercises designed in sitting and standing position is a low level intensity exercise done to activate the core muscle (internal oblique, external oblique, transverse abdominis, pelvic floor) that are stretched during pregnancy. This co-activation of core muscles imparts active stiffness through thoracolumbar fascia to the lumbar spine and thereby reducing the exaggerated lumbar lordosis which is considered to be one of the causes for lumbar pain during pregnancy [27,28]. Like any other joints in the human body, range of motion and core activation around pelvic joints need to be maintained as well.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the applications of our device also extend beyond pre-operative THA planning. Due to the complex interplay between lumbar and pelvic mobility, pelvic movements may also play a key role in chronic back pain; one of the leading causes of disability worldwide [38][39][40], and thus our device may enable identification of potentially pathological pelvic movement patterns which can be targeted via physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also suggested that posterior pelvic tilting would help to reduce the lordotic curvatures. Result of the studies have demonstrated that properly trained pelvic tilting maneuver produce voluntary rotation of the pelvis and produce sufficient amount of alteration in the lordotic curvatures (Minicozzi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%